Entropy generation rate in turbulent spots in a boundary layer subject to freestream turbulence - Rehill, Brendan; Walsh, Ed J.; Nolan, Kevin; Mceligot, Donald M.; Brandt, Luca; Schlatter, Philipp; Henningson, Dan S. (IUTAM Bookseries, 2010)
Turbulent spots are studied in a boundary layer subject to freestream turbulence with the data taken from direct numerical simulations performed by Brandt et al.[2]. Additional simulations of artificially induced turbulent spots are investigated in a laminar and streaky boundary layer. The flow is seperated into turbulent and non-turbulent regions using a threshold of spanwise velocity, w. Mean velocity profiles within the spot show siginificant deviations from fully turbulent profiles. The dissipation coefficient, indicating the evolution of entropy generation within the spot, shows good agreement with previous correlations. © 2010 Springer Science+Business Media B.V.
CRIS-Team Scopus Importer:2023-03-21